Role of Remittance on Socio-economic Status of Peri-urban Households of Kathmandu - Rana , Anil (THE ACADEMIA, 2026)
International labor migration has become a central livelihood strategy in Nepal, with remittances playing a critical role in sustaining household economies and supporting national development. This study examines the socio-economic impact of remittances on peri-urban households in Chandragiri Municipality, Ward No. 13 of Kathmandu District, using primary data collected from 60 migrant households in 2023. A descriptive cross-sectional research design was employed, supported by secondary data from government and international migration reports. The findings indicate that remittances significantly improved household income, asset ownership, living standards, and social status. Migrant households experienced reduced debt burdens, increased consumption of nutritious food, and greater investment in land, housing, and durable goods. However, the majority of migrants were engaged in low-skilled employment in Gulf countries and Malaysia, reflecting limited educational attainment and restricted access to higher-paying jobs. This pattern suggests that while remittances provide important short-term economic benefits, their long-term developmental impact remains constrained by skill deficits and labor market vulnerability. The study concludes that remittances are a vital source of livelihood security for peri-urban households in Kathmandu but emphasizes the need for policies that promote skills development, financial literacy, and productive investment in order to transform migration from a survival strategy into a pathway for sustainable socio-economic development.